Influence Of Organizational Culture And Innovative Behavior Toward Employee Performance In Tandes District City Of Surabaya, East Java - Handayani, Tutik; Wijayanti W2, Dewie Tri; Kistyanto, Anang (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Quality public service needs to be demonstrated by employees. Good employee performance in providing quality public services can increase public satisfaction. Employees who perform well will be able to provide efficient, responsive and professional services, so that people feel heard and well served. This research aims to analyze and prove the influence of organizational culture and innovative behavior on employee performance in Tandes District, Surabaya City. The research results show that factors consisting of organizational culture and innovative behavior have a real influence simultaneously (together) on employee performance in Tandes District, Surabaya City. Factors consisting of organizational culture and innovative behavior have a real influence partially (individually) on employee performance in Tandes District, Surabaya City. Among the factors consisting of organizational culture and innovative behavior, it turns out that organizational culture has a dominant influence on employee performance in Tandes District, Surabaya City, with a partial influence of 0.623. It is recommended to improve performance oriented towards community services with the principle of placing community needs and satisfaction as the main priority, implementing fast, easy and transparent public services, providing fast and appropriate responses to community complaints, building effective communication and empathy with the community.